Fugitive son : a memoir - Calderón, Aramís ([Lincoln] : Potomac Books, an imprint of the University of Nebraska Press, 2024)
In this compelling memoir Aramís Calderón tells a fascinating story of what it's like to be a fugitive's son, what drives a young man into the military, and how his time in combat brings back childhood memories he'd hoped to forget.
Cover Page -- Title Page -- Copyright Page -- Dedication -- Acknowledgments -- A Note on Translation -- 1 -- 2 -- 3 -- 4 -- 5 -- 6 -- 7 -- 8 -- 9 -- 10 -- 11 -- 12 -- Epilogue
JSTOR
Keywords: Calderón, Aramís.; Children of criminals; Fugitives from justice; Enfants de criminels; Fugitifs recherchés par la justice; BIOGRAPHY & AUTOBIOGRAPHY